(untitled) (Medico Legal Update, 2021)
Background: The Covid-19 pandemic has spread to 215 countries and territories since the outbreak first occurred in Wuhan, China. Indonesia has also declared the Covid-19 national disaster since 2 positive patients were found on March 2, 2020 and there has been a rapid spread to various regions in Indonesia including Banyumas District. This study aims to determine the risk factors, effective reproduction number and predictions SIR of Covid-19 in the Banyumas District for the period of 16 March - 14 June 2020. Method: This study is a cross-sectional design. Cases are patients with comfirmed covid-19 in the area. Minimum sample size was 43 and total sample size was 70 people. Univariate analysis was used to describe of characteristics, epiestim to determine effective reproduction number, and SIR model to determine prediction of covid-19. Result: As of June 14, 2020, in Banyumas District there were 392 suspected cases, 70 confirmed cases, 58 cases were recovered and 4 people died. The characteristics of the confirmed cases were the age group of 15-24 years as much as 21.1%, males 62%, 52.1% have a history of travel to/from out of town, and 91.5% showed symptoms especially fever symptoms as much as 81.7%. The effective reproduction number (Rt) for the period March 16, 2020-June 14, 2020 was 1.81 (0.83-3.35; 95% CrI). SIR model predictions, that the peak of the outbreak will occurred on June 21, 2020 with the number of confirmed cases of 4,312 people. Conclusions: The covid-19 outbreak in Banyumas District was still out of control and still ongoing. It is recommended to continue to increase discipline of health protocols, get used to wearing masks, keep a distance and wash hands with soap and strengthen tests, traces and treatments and also protect vulnerable groups.